KEUNGGULAN KURIKULUM DAN PROGRAM DI SMAS PLUS ASSA’ADAH DAHU SERANG - Diva Agustiani; Fatiroh; Faizah Budi Rahayu; Dini Zakiyatul (Jurnal Studi Pesantren, 2026)
This study aims to analyze the advantages of curriculum and educational programs at SMAS Plus Assa’adah Dahu Serang, a private Islamic-based school that integrates the Merdeka Curriculum with the pesantren curriculum. This research employed a qualitative method through interviews and library research. The findings reveal that the integrated curriculum provides a holistic learning experience by emphasizing academic achievement alongside religious, moral, and character development. The dominant teaching strategy is student-centered learning combined with Project Based Learning (PBL), which encourages creativity, collaboration, and 21st-century skills. The assessment model covers cognitive, affective, and psychomotor domains, while technology integration enhances the effectiveness of learning and prepares students for the digital era. Moreover, various flagship programs such as extracurricular activities, academic and non-academic guidance, as well as partnerships with higher education institutions, support students’ academic and personal growth. These findings highlight that the integrated curriculum and innovative programs at SMAS Plus Assa’adah can serve as an alternative model for improving educational quality that balances academic, social, and spiritual dimensions.